(untitled) (Swiss Medical Weekly, 2017)
Bariatric surgery is an effective treatment of type 2 diabetes in obese patients. The obesity epidemic does not spare patients with type 1 diabetes mellitus (T1DM), but there is no consensus regarding the role of surgery in the management of obese T1DM patients. Published data consistently report significant weight loss after surgery in obese T1DM patients, but long-term glycaemic control remains difficult to achieve. Here we present our experience with a challenging patient and a review of the literature. Our patient successfully underwent a roux-en-Y gastric bypass (RYGB) when she was 28 years old. Five years after surgery, she was diagnosed with latent autoimmune diabetes of adults and insulin therapy was initiated. Insulin therapy proved very difficult to adjust, with frequent episodes of postprandial hyperglycaemia. These difficulties could only be overcome by the initiation of a subcutaneous insulin infusion using a sensor-augmented insulin pump with automated suspension. This change allowed better glycaemic control. Despite considerable weight loss with a concomitant decrease in insulin requirement, glycaemic control remained difficult after surgery. Due to their different impacts on glucose kinetics, the type of surgical operation should be part of the assessment. These patients might benefit from sensor-augmented insulin pump therapy with automated insulin suspension after bariatric surgery. The decision for surgical intervention in these patients should be carefully weighed against the difficulties in achieving adequate glycaemic control.